Smartphone addiction and adolescent mental health: a cross-sectional study in West Sumatra province - Sarfika, Rika; Wijaya, Ahmad; Putri, Zifriyanthi Minanda; Saifudin, I Made Moh. Yanuar (Intelektual Pustaka Media Utama, 2024)
In West Sumatra Province, Indonesia, approximately 13.01% of individuals aged 15 years or older are affected by mental and emotional disorders, ranking it as the third highest among the 34 provinces. Excessive smartphone use has emerged as a potential influencer of mental health, associated with social networking addiction, shyness, and low self-esteem. This study aimed to examine the relationship between smartphone addiction and mental health issues in adolescents using a cross-sectional design. The sample included 283 randomly selected students aged 15-17 years. Smartphone addiction was measured using the smartphone addiction scale-short version (SAS-SV), and mental health was assessed using the strength and difficulties questionnaire (SDQ). The study revealed a significant association (p<0.001) between smartphone addiction and mental health problems among adolescents, with 72.1% of respondents experiencing smartphone addiction and 26.9% classified as having abnormal mental health. These findings emphasize the need for increased awareness regarding the negative impact of excessive smartphone use on adolescent mental health. Schools should play a vital role in addressing this issue through the provision of guidance and counseling services. Future research should investigate causal relationships using longitudinal designs and consider diverse populations to enhance the generalizability of the results.